Effect of Sling Exercise Therapy and Meridian Plucking Manipulation on Rehabilitation of Pulmonary Function and Life Quality in Patients With Stroke - Xiang LI; Li LI; Yunfeng CHEN; Hongrui ZHANG; Shuai YANG; Xianzhang YANG (康复学报)
Objective:To explore efficacy of sling exercise therapy and meridian plucking manipulation on rehabilitation of pulmonary function and life quality of patients with stroke in the recovery period.Methods:A total of 120 patients with stroke were randomly divided into sling exercise therapy and meridian plucking manipulation group, respiratory training group and control group, with 40 cases in each group. The control group was treated with routine rehabilitation training and nursing care, respiratory training group exercised breathing training on the basis of the control group, another group was treated with sling exercise therapy and meridian plucking manipulation on the basis of the control group. After four weeks of treatment, lung function tests were performed to evaluate the lung function of the patients, SF-36 scale was used to evaluate the quality of life of the patients.Results:At the end of four weeks of therapy, the prevalence of FEV1, FVC, and SF-36 in the three groups were all higher than those before treatment, the difference was statistically significant (P<0.05), The sling exercise and meridian plucking manipulation group was better than other groups (P<0.05).Conclusion:Sling exercise therapy and meridian plucking manipulation can improve the lung function and life quality of patients effectively.